Sequence-dependent electrical response of ssDNA-decorated carbon nanotube, field-effect transistors to dopamine - Salila Vijayalal Mohan, Hari Krishna (2017)
Single-walled carbon nanotube (SWCNT)-based field-effect transistors (FETs) have been explored for use as biological/chemical sensors. Dopamine (DA) is a biomolecule with great clinical significance for disease diagnosis, however, SWCNT FETs lack responsivity and selectivity for its detection due to the presence of interfering compounds such as uric acid (UA). Surface modification of CNTs using single-stranded deoxyribonucleic acid (ssDNA) renders the surface responsive to DA and screens the interferent. Due to the presence of different bases in ssDNA, it is necessary to investigate the effect of sequence on the FET-based molecular recognition of DA. SWCNT FETs were decorated with homo- and repeated-base ssDNA sequences, and the electrical response induced by DA in the presence and absence of UA was gauged in terms of the variation in transistor electrical parameters including conductance, transconductance, threshold voltage and hysteresis gap. Our results showed that the response of ssDNAdecorated devices to DA, irrespective of the presence or absence of UA, was DNA sequence dependent and exhibited the trend: G > A > C and GA > GT > AC > CT, for homo- and repeated-base sequences, respectively. The different response of various SWCNT–ssDNA systems to DA underlines the sequence selectivity, whereas the detection of DA in the presence of UA highlights the molecular selectivity of the ssDNA-decorated devices.